2005
DOI: 10.4049/jimmunol.174.2.646
|View full text |Cite
|
Sign up to set email alerts
|

LIGHT Is Constitutively Expressed on T and NK Cells in the Human Gut and Can Be Induced by CD2-Mediated Signaling

Abstract: The TNF superfamily cytokine, lymphotoxin-like inducible protein that competes with glycoprotein D for binding herpesvirus entry mediator on T cells (LIGHT; TNFSF14), can augment T cell responses inducing IFN-γ production and can drive pathological gut inflammation when expressed as a transgene in mouse T cells. LIGHT expression by human intestinal T cells suggests the possibility that LIGHT may play a key role in regulation of the mucosal immune system. A nonenzymatic method was developed for the isolation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 48 publications
5
49
1
1
Order By: Relevance
“…27 Studies in animal models suggest that LIGHT signaling pathways may be crucial for the development of various autoimmune disorders, at least in part because of their effects on T cells (eg, increased production of interferon-␥) and T-cell homing into inflamed tissues. 28,29 In the present study, we extend these findings, showing profound effects of LIGHT on THP-1 macrophages that lead to enhanced lipid accumulation and increased levels of prothrombotic mediators. Importantly, a similar LIGHT-induced pattern was also seen in human monocyte-derived macrophages.…”
Section: Discussionsupporting
confidence: 65%
“…27 Studies in animal models suggest that LIGHT signaling pathways may be crucial for the development of various autoimmune disorders, at least in part because of their effects on T cells (eg, increased production of interferon-␥) and T-cell homing into inflamed tissues. 28,29 In the present study, we extend these findings, showing profound effects of LIGHT on THP-1 macrophages that lead to enhanced lipid accumulation and increased levels of prothrombotic mediators. Importantly, a similar LIGHT-induced pattern was also seen in human monocyte-derived macrophages.…”
Section: Discussionsupporting
confidence: 65%
“…Human NK cells expressing TNFSF14 have previously been observed in the gut, where its expression is constitutive (38). Our results demonstrate its very rapid induction on peripheral blood-derived NK cells in response to a variety of stimuli.…”
Section: Discussionsupporting
confidence: 57%
“…It would seem logical that NK cells would contribute to inflammation within the intestinal tract during CLPinduced injury. The intestinal wall contains large numbers of NK cells in subepithelial regions as well as in the lamina propria (16). Several studies have shown that NK cells contribute to intestinal inflammation during enteric infections and inflammatory bowel disease (17)(18).…”
Section: Discussionmentioning
confidence: 99%